Santa clause 2 - Reilly, Brian (Brian M.); Newmyer, Robert; Silver, Jeffrey; Rhymer, Don.; Lembeck, Michael; Allen, Tim, 1953-; Reinhold, Judge, 1957-; Crewson, Wendy; Mitchell, Elizabeth, 1970-; Krumholtz, David, 1978-; Lloyd, Eric.; Breslin, Spencer; et al. (Burbank, CA : Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2003)
Scott Calvin has been Santa Claus for the past eight years, and his elves consider him the best ever. But Santa's world is turned upside down when his son gets on the naughty list, and if Scott doesn't marry soon, he'll stop being Santa forever.
Santa clause 2 -- Operation toy box: save Santa -- Inside the North Pole with Curtis -- True confessions of the legendary figures.
Bonus features: Inside the North Pole with Curtis; director's tour of Elfsburg; gag reel; DVD-ROM; true confessions of the legendary figures; audio commentary; deleted scenes; Operation Toybox: Save Santa game.
Special features: "Naughty and nice" set-top game; North pole commentary with Tim Allen as Santa and Spencer Breslin; tour of the North Pole; "Legendary figures"--Interviews with Tooth Fairy, Mother Nature, Father Time, Easter Bunny; special effects featurette; deleted scenes/gag reel; Hilary Duff music video; E-cards.
Director of photography, Adam Greenberg ; editor, David Finfer ; music, George S. Clinton ; costume designer, Ingrid Ferrin ; production designer, Tony Burrough ; special character effects designed and created by Alec Gillis, Tom Woodruff, Jr.
Tim Allen, Judge Reinhold, Wendy Crewson, Elizabeth Mitchell, David Krumholtz, Eric Lloyd, Spencer Breslin, Kevin Pollak, Molly Shannon.
MPAA rating: G.
DVD, region 1; Dolby digital 5.1 surround; fullscreen (aspect ratio: 1.33:1).
Keywords: Santa Claus -- Drama; Fathers and sons -- Drama; Families -- Drama; Christmas films; Fiction films; Feature films; Films for the hearing impaired